Bioinspired study of energy and electron transfer in photovoltaic system - Moniruddina, Md.; Ilyassov, B.; Seliverstova, E.; Shabdan, Y.; Bakranov, N.; Ibrayev, N.; Nuraje, N. (Journal of Experimental Nanoscience, 2017)
This study focuses on understanding the fundamentals of energy transfer and electron transport in photovoltaic devices with uniquely designed nanostructures by analysing energy transfer in purple photosynthetic bacteria using dye-sensitised solar cell systems. F€orster resonance energy transfer between the xanthene dye (donor of energy) and a new polymethine dye (acceptor of energy) was studied in dye-sensitised solar cells, which leads to a doubling of energy conversion efficiency in comparison to the cell with only the polymethine dye. The electron transport in the two different nanostructures of zinc oxide (nanorods and nanosheets) was investigated by spectroscopic methods (UV-vis spectrometer, time-resolved photoluminescence spectroscopy) and electrochemical potentiostat methods. The nanosheet structure of zinc oxide showed high short circuit current and long diffusion length. This fundamental study will lead to efficient artificial photosystem designs.
Keywords: Bioinspired study; energy; electron transfer; photovoltaic system